2012
DOI: 10.1111/j.1369-7625.2012.00779.x
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding piecemeal research on participation in cervical cancer screening: the advantages of a social identity framework

Abstract: Background Cervical cancer screening research has predominantly focused on one type of participation, namely compliance with medical recommendations, and has largely ignored other types of participation. While there is some research that has taken a different approach, findings in this research area are not well integrated under a theoretical framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 109 publications
(177 reference statements)
0
4
0
Order By: Relevance
“…For example, Bowen and colleagues (2003) found that increased social identity positively predicted interest in breast cancer screening. Also, social identity and social relationships with physicians, family, or friends, as well as belongingness, are important in improving cervical cancer screening rates (Tribe and Webb 2014). Social identity also influences clinical outcomes for members of at-risk groups.…”
Section: Social Identity and Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Bowen and colleagues (2003) found that increased social identity positively predicted interest in breast cancer screening. Also, social identity and social relationships with physicians, family, or friends, as well as belongingness, are important in improving cervical cancer screening rates (Tribe and Webb 2014). Social identity also influences clinical outcomes for members of at-risk groups.…”
Section: Social Identity and Healthmentioning
confidence: 99%
“…Emerging theoretical and empirical work suggests social identity may be an important tool for developing psychosocial explanations of geographical health inequalities (Haslam et al 2009;Tribe and Webb 2014). The direct and indirect effects of social identity on health can be elicited through a contextual approach that bridges unequal social structures (e.g., financial resources, health care access) and individual experiences (Bolam, Murphy, and Gleeson 2006).…”
Section: Social Identity and Healthmentioning
confidence: 99%
“…The goal of the second is to ensure there are not systematic differences between who is screened and who is not. The usual response in the literature to both of these goals is to promote higher screening uptake, whether in the population as a whole for the purpose of reaching targets or in specific groups who have been identified as underscreened for the purpose of reducing disparity [ 9 , 21 23 ]. In the cervical screening literature, reducing disparity is often referred to in terms of increasing equity or something like it [ 9 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Social identity, or a sense of belonging to a place is relevant to health, as it is known to be associated with health outcomes, such as intention to perform breast screening and progression of disease, such as HIV . Moreover, research among older adults found that collective self‐esteem (an individual's self‐evaluation as a member of social groups) is a protective factor against chronic conditions .…”
mentioning
confidence: 99%